Enhancing analytical reading and writing skills in ESL for vocational students: A hybrid instruction of collaborative learning and task-based learning teaching - Xuyang, Chen; Jantharajit, Nirat; Thongpanit, Phichittra (Asian Journal of Contemporary Education, 2024)
This study delves into the efficacy of collaborative learning (CL) in nurturing critical thinking, bolstering reading comprehension, and fostering effective communication within diverse educational settings. It further investigates the constructive role of task-based learning teaching (TBLT) in elucidating learning objectives, bolstering motivation, and refining analytical reading and writing proficiencies. Drawing upon social constructivism and language acquisition theory, the research proposes an integrated instructional approach that melds CL with TBLT to cultivate vocational students’ analytical reading and writing skills. This instructional methodology comprises nine sequential steps: establishing learning objectives, task selection, group formation, task clarification, provision of resources and support, supervision, encouragement of interaction, assessment of learning outcomes, and iterative adjustment. Moreover, the study underscores the imperative of tailoring English language pedagogies to suit the unique requirements of non-English speaking contexts. Instructional strategies which integrate CL with TBLT are theorized to be effective in promoting analytical reading and writing skills in vocational students. The study emphasize the adaptation of teaching strategies to diverse linguistic contexts, and promoting inclusive learning environments tailored to non-English speaking countries’ needs.